A New Approach to the Synthesis of meso‐CN‐Substituted BODIPYs. Issue 7 (25th May 2016) - Yakubovskyi, Viktor P.; Didukh, Natalia O.; Zatsikha, Yuriy V.; Kovtun, Yuriy P.
Abstract: A preparative synthetic procedure to the meso ‐CN substituted BODIPY has been developed. This method is based on the addition of KCN to the borondipyrromethene moiety of the meso ‐unsubstituted molecules in the presence of a crown ether with further oxidation with Pb(OAc)4 . The CN group at this position causes an essential bathochromic shift in absorption/emission and influence on other physicochemical properties of borondipyrromethenes over a wide range. Abstract : A preparative synthetic procedure to the meso ‐CN substituted BODIPY has been developed. This method is based on the addition of KCN to the borondipyrromethene moiety of the meso ‐unsubstituted molecules in the presence of a crown ether with further oxidation with Pb(OAc)4 . The CN group at this position causes an essential bathochromic shift in absorption/emission and influence on other physicochemical properties of borondipyrromethenes over a wide range.